Laparoscopic right colectomy: Miles away or just around the corner? - Lotti, Marco (J Minim Access Surg, 2016)
BACKGROUND: Despite the drive toward centralization of surgery in high-volume centers, the majority of colectomies are still performed by low- or medium-volume surgeons. MATERIALS AND METHODS: A modification of the technique of laparoscopic right colectomy (LRC) originally described by Young-Fadok and Nelson was developed. The key points of that technique were maintained, but a different port-site layout and a counterclockwise approach were adopted, to warrant better trocar triangulation, to reduce the need of right colon manipulation and to avoid dissection along false planes. This modified technique was applied in 82 patients by 16 surgeons with no previous experience in LRC. RESULTS: Average operative time was 125 ± 35 min. Conversion occurred in 10 cases (12.2%). Grade III postoperative complications occurred in 3 patients (3.6%). No postoperative mortality was observed. Average number of lymph nodes retrieved was 19 ± 6. Average length of stay was 7 ± 4 days. CONCLUSION: Providing low-volume surgeons with simplified and easy-to-learn surgical techniques could improve outcomes and lead to an increased use of laparoscopy.